SEJARAH BAHASA SEMITIK DAN THE CLASH OF LANGUAGE - Ahmad Falhan (STAI DI AL-HIKMAH, 2024)
The discussion of Semitic languages ??can be categorized into two parts, the first is a general discussion in history, development and its scope. The second is a special discussion, about sounds, sounds, rules and vocabulary of Semitic languages ??which include the nature of Semitic languages ??in the washfiyah. In this paper, the author examines the first part of the discussion about the history of Semitic languages, historical study, as well as the process of the spread of the language, the clashes and its influence on the beginning of the development of other languages. The research method used is qualitative with a literature study approach from books, journals, and various relevant research results. The conclusion of the study is that the original Semitic language is the parent of several languages ??in the world. Among these languages, some are still alive today such as Arabic and Hebrew, some are dead or no longer have speakers, but traces can still be seen in the inscriptions they wrote such as Sumerian, Akkadian, Assyrian, Canaanite (Kan'aniyyah), Aramaic (Aramia), and Phinesia. There is also an opinion that can be relied upon, namely the opinion of most orientalists such as Sprenger (1813-1893), Goideh, Keitani, Moscati, Finkir, Eberhard Schrader (1836-1908) etc., they considered that the plains of the Arabian peninsula were the origin of their region. Semitic languages ??have had a lot of influence on languages ??other than Semitic languages. Like the Sumerians, the native people of Babylonia had made Semitic their language, although Sumerian also had a lot of influence on Semitic languages. There are many similarities within the Semitic language family which are the result of the influence caused by the process of assimilation and clash of cultures and languages